Nova metoda hodnoceni spektralni analyzy variability srdeeni frekvence - Stejskal, P.; Slachta, R.; Elfmark, M.; Salinger, M.; Gaul-Alacova, P. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2002)
Individual indices of spectral analysis (SA) of heart rate variability (HRV), which are used to diagnose the autonomic nervous system (ANS) activity, often give somewhat inconclusive and antagonistic results. Based on the results of age dependence (.lachta et al., 2002), and dependence of exercise intensity (Stejskal et al., 2001) on the short-term SA HRV, the authors developed a new evaluation procedure. It consists of three complex indexes, which combine all age dependent parameters gained from the orthoclinostatic test: complex index of vagal activity, complex index of sympatho-vagal balance, and total score of SA HRV. The total score-to-age ratio was designated as the so-called functional age of ANS. The new evaluation method enables easier orientation in the comparison of standard parameters, simpler interpretation of the results, and clear identification of less perceptible changes in the power spectrum.